2018
DOI: 10.1093/rheumatology/key357
|View full text |Cite
|
Sign up to set email alerts
|

The temporal relationship between cancer and adult onset anti-transcriptional intermediary factor 1 antibody–positive dermatomyositis

Abstract: Objectives To characterize the 10 year relationship between anti-transcriptional intermediary factor 1 antibody (anti-TIF1-Ab) positivity and cancer onset in a large UK-based adult DM cohort. Methods Data from anti-TIF1-Ab-positive/-negative adults with verified diagnoses of DM from the UK Myositis Network register were analysed. Each patient was followed up until they developed cancer. Kaplan–Meier methods and Cox proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 17 publications
6
56
0
2
Order By: Relevance
“…Conversely TRIM3 has tumour suppressor activity, inhibiting the growth of liver, colorectal and gastric cancer (Boulay et al, 2009). The presence of autoantibodies against cancerassociated TRIMs accords with the strong temporal association between myositis and the development of malignancies in adult-onset anti-TIF1γ positive DM (Oldroyd et al, 2019), consistent with the high proportion of cancer-associated myositis cases in the current study (45%). Overall, the expanded targeting of TRIM proteins we observed in DM plasma supports the role of the TRIM RING-type E3 ubiquitin ligase subfamily as powerful regulators of the immune system through post-translational modification (Hage and Rajsbaum, 2019;van Tol et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Conversely TRIM3 has tumour suppressor activity, inhibiting the growth of liver, colorectal and gastric cancer (Boulay et al, 2009). The presence of autoantibodies against cancerassociated TRIMs accords with the strong temporal association between myositis and the development of malignancies in adult-onset anti-TIF1γ positive DM (Oldroyd et al, 2019), consistent with the high proportion of cancer-associated myositis cases in the current study (45%). Overall, the expanded targeting of TRIM proteins we observed in DM plasma supports the role of the TRIM RING-type E3 ubiquitin ligase subfamily as powerful regulators of the immune system through post-translational modification (Hage and Rajsbaum, 2019;van Tol et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Individuals with autoantibodies targeting the cytoplasmic nucleic acid sensor MDA5 (also called interferon induced with helicase C domain 1, IFIH1) can present with rapidly progressive interstitial lung disease which is associated with high mortality (Abe et al, 2017;Betteridge et al, 2019). Several members of the tripartite motif (TRIM) protein family are known autoantibody targets in IIM, and there is a strong temporal association between adult-onset dermatomyositis and malignancy onset in individuals with antibodies to transcription intermediary factor 1γ (TIF1γ, TRIM33) (Oldroyd et al, 2019). Many TRIM proteins are important immune regulators (van Tol et al, 2017;Versteeg et al, 2014), and dysregulation of TRIM proteins leading to reduced ability to restrict viral infection has been reported in several autoimmune diseases, including systemic lupus erythematosus and inflammatory bowel disease (Oke et al, 2009;Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There is a case report on ovarian cancer complicating DM in a patient with a breast cancer susceptibility gene (BRCA) mutation. 18 Although few studies have reported on the sites of malignancy in anti-TIF1-c Ab-positive DM patients, 19 our study observed a high frequency of ovarian and breast cancer in patients with Anti-TIF1-c Ab, anti-transcriptional intermediary factor 1-c antibody; CADM, clinically amyopathic dermatomyositis; CAM, cancer-associated myositis; CI, confidence interval; CK, creatine phosphokinase; ILD, interstitial lung disease.…”
Section: Discussionmentioning
confidence: 49%
“…In all patients, the Ab titer decreased by 50% or more; in addition, three of four patients demonstrated a negative final Ab test. In contrast, eight patients had advanced stages of malignancy (patients [16][17][18][19][20][21][22][23]. Three patients (patients 16, 22 and 23) were treated for DM and not for malignancy.…”
Section: Clinical Significance Of Longitudinal Changes Of Anti-tif1-cmentioning
confidence: 99%
“…The strong association and close temporal relationship between anti-TIF-1c Ab and the onset of cancer in adult DM patients have been wellestablished. 25,26 A recent systematic review and meta-analysis confirmed that anti-TIF-1c Ab could be a valuable tool for diagnosing cancerassociated DM, with a pooled sensitivity of 52%. 27 In our study, the association between anti-CRT Ab positivity and cancer occurrence was not as strong as that of anti-TIF-1c Ab.…”
Section: Discussionmentioning
confidence: 99%